Supporting transition to law school and student well-being : the role of professional legal identity. - Field, Rachael; Duffy, James; Huggins, Anna (International Journal of the First Year in Higher Education v.4 n.2 p.15-25 https://doi.org/10.5204/intjfyhe.v4i2.167, 2013)
The empirically established decline in law student well-being during the first year of law school is a red-flagged imprimatur for first year curriculum change. This article suggests that by engaging law students with the concept of a positive professional identity, student engagement and intrinsic motivation will increase because they are working towards a career goal that has meaning and purpose. Law school is a time of professional transformation and the legal academy can take steps to ensure that this transformation is inculcated with positive messages. Literature from the fields of law and psychology is analysed in this article, to explain how a positive conception of the legal profession (and a student's future role within it) can increase a student's psychological well-being - at law school and beyond. [Author abstract]